Extended glaze firing improves flexural strength of a glass ceramic - Aurelio, Iana L.; Fraga, Sara; Dorneles, Lucio S.; Bottino, Marco A. [UNESP]; May, Liliana G. (Elsevier B.V., 2015)
Objective. To investigate the effect of firing protocols on flexural strength, surface roughness, and crystalline structure of a leucite-based glass ceramic. Methods. Discs produced by automated machining were distributed into five groups (n=30) according to the applied firing protocols, conducted above (790 degrees C) or below (575 degrees C) the ceramic transition temperature (T-g) (625 +/- 20 degrees C): C - control, no heat treatment; G790 glaze firing (790 degrees C) for 1.5 min (manufacturer-recommended); G790-SC-G790 modified by slow cooling; EGF790-SC-extended G790 for 15 min, with slow cooling; and EF575-SC-extended firing below T-g at 575 degrees C for 15 min, with slow cooling. Discs were subjected to biaxial flexural tests and results were assessed using Weibull analysis. Surface roughness was measured before and after treatments. One specimen from each group was used for X-ray diffraction (XRD). Results. Highest values of characteristic strength (sigma(0)) were obtained for EGF790-SC (211.7 MPa). Regimens EF575-SC, G790-SC, and G790 produced sigma(0) values (167.9, 157.7, and 153.7 MPa, respectively) lower than the control (C) (187.7 MPa). The Weibull modulus (m) was statistically similar between groups. All treatments reduced the mean roughness (Ra) of the specimens. Extended cycles (EGF790-SC, EF575-SC) decreased the mean amplitude (Rz). XRD revealed no crystalline phase transformation and slight changes in size of leucite crystallites. Significance. Increased values of fracture strength and decreased surface roughness for a leucite-reinforced glass ceramic are achieved by extended glaze firing after machining. Crystalline structure is not modified. Glaze cycles, manufacturer-recommended or modified by slow cooling, and firing below T-g, significantly reduce fracture strength. (C) 2015 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Glass ceramic; Leucite; CAD/CAM; Machining; Roughness; Thermal cycle; Glaze; Biaxial flexure strength